Oxygen Use in Neonatal Care: A Two-edged Sword - Perrone, Serafina; Bracciali, Carlotta; Di Virgilio, Nicola; Buonocore, Giuseppe (Frontiers in Pediatrics, 2017)
In the neonatal period, the clinical use of oxygen should be taken into consideration for its beneficial and toxicity effects. Oxygen toxicity is due to the development of reactive oxygen species such as OH∙ that is one of the strongest oxidants in nature. Of note, generation of reactive oxygen species is a normal occurrence in human and it is involved in a myriad of physiological reactions. Anyway an imbalance between production of oxidant species and antioxidant defenses, called oxidative stress, could affect various aspect of organisms' physiology and it could determine pathological consequences to living beings. Neonatal oxidative stress is essentially due to decreased antioxidants, increased ROS or both. Studies have demonstrated that antioxidant capacity is lower in preterm newborns than term babies. This well known deficiency of antioxidant factors is only a piece of a cohort of factors which can be involved in the neonatal oxidative stress and the increased production of ROS may be a main factor. Mechanisms of ROS generation are: mitochondrial respiratory chain, free iron and Fenton reaction, inflammation, hypoxia and/or ischemia, reperfusion and hyperoxia. Oxidative stress following hyperoxia has been recognized to be responsible for lung, central nervous system, retina, red blood cell injuries and possibly generalized tissue damage. When supplemental oxygen is needed for care, it would be prudent to avoid changes and fluctuations in SpO2. The definition of the safest level of oxygen saturations in the neonate remains an area of active research. Based on all the actually available evidence, the most prudent approach would be to set alarm limits between 90-95%. It should allow to avoid SpO2 values associated with potential hypoxia and/or hyperoxia. Although the usefulness of antioxidant protection in the neonatal period is still under investigation, the risk of tissue damage due to oxidative stress in perinatal period should not be underestimated.